Peningkatan Motivasi Entrepreneurship Bagi Santri Tahfidzul Qur’an Pondok Pesantren Salafiyyah Syafi’iyyah Sukorejo Situbondo - Ahmad Royhan Firdausy; Ahmad Muzayyin (Civiliza Publishing, 2026)
The tahfidzul Qur’an students of Pondok Pesantren Salafiyyah Syafi’iyyah Sukorejo are an important asset for bringing about positive change in the community. However, the lack of motivation and insufficient entrepreneurship material have become issues that need to be addressed. Because this reduces its role to mere memorization. This community service uses the ABCD (Asset Based Community Development) method, which is conducted through the provision of materials using lecture and discussion techniques.The results of this community service show, first, a change in the mindset of the tahfidzul Qur’an students towards being more